The Natural Sweetener Stevia: An Updated Review on its Phytochemistry, Health Benefits, and Anti-diabetic Study - Patel, Shraddha; Navale, Archana (Current Diabetes Reviews, 2024)
Stevia rebaudiana Bertoni is one of the significant high qualities of non-caloric sugar substitute sweetener plants against diabetes disease. Diabetes mellitus is one of the most common metabolic diseases caused by insulin secretion defects, insulin resistance in peripheral tissues, or both. Stevia rebaudiana is a perennial shrub of the Compositae family that is grown in several places around the world. It contains a plethora of different bioactive constituents which are responsible for several activities and sweetness. This sweetness is due to the presence of steviol glycosides which is 100-300 times sweeter than sucrose. Furthermore, stevia reduces oxidative stress, lowering the risk of diabetes. Its leaves have been used to control and treat diabetes and a variety of other metabolic diseases. This review summarizes the history, bioactive constituents of S. rebaudiana extract, pharmacology, anti-diabetic activity, and its application, especially in food supplements.
Keywords: health benefits